Marine Climate and Climate Change Storms, Wind Waves and Storm Surges - Weisse, Ralf.; Storch, Hans.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Marine environmental conditions such as storms, storm surges and wave heights are directly experienced by, for example, off-shore operations or coastal populations. The authors review and bring together the state-of-the-art and present day knowledge about historical changes, recent trends and concepts on how marine environmental conditions may change in the future as well as discuss models and data problems.
Climate and climate variability -- Marine weather phenomena -- Models for the marine environment -- How to determine long-term changes in marine climate -- Past and future changes in wind, wave, and storm surge climates.
Keywords: Geography; Earth Sciences; Earth Sciences, general